Cover, Volume 43, Issue 3. Issue 3 (22nd February 2022) - Gao, Yang; Wu, Huan; Xu, Yuping; Shen, Qunshan; Xu, Chuan; Geng, Hao; Lv, Mingrong; Tan, Qing; Li, Kuokuo; Tang, Dongdong; Song, Bing; Zhou, Ping; et al.
Abstract : The cover image is based on the Research Article Novel biallelic mutations in SLC26A8 cause severe asthenozoospermia in humans owing to midpiece defects: Insights into a putative dominant genetic disease by Xiaojin He et al., https://doi.org/10.1002/humu.24322 .